Processes and outcomes of a communalization of trauma approach: Vets & Friends community‐based support groups. Issue 7 (28th January 2021) - Balmer, B R.; Sippola, John; Beehler, Sarah
Abstract: Veterans often experience challenges related to processing traumatic experiences and community reintegration, yet there is a dearth of research on promising community‐driven approaches. This paper describes core processes and outcomes of Vets & Friends (V&F), a community‐based support program that promotes veteran reintegration by healing trauma and moral injury using a communalization of trauma (CoT) approach. We conducted focus groups with 23 V&F group members. A mix of inductive and deductive codes were generated during thematic analysis. Critical themes identified included processes such as sharing narratives, connecting emotionally with experiences, feeling heard and accepted by group members, and listening as others shared their experiences. Outcomes included restoration of trust, connection with group members, building skills to manage trauma, and community acceptance and engagement. V&F shows promise in meeting veteran‐specific needs by employing CoT approaches that offer opportunities to restore community trust and acceptance.